Environmental influence and intention to quit smoking among college students - Zainal Abidin, Muhammad 'Adil; Kadir@Shahar, Hayati; Abdul Manaf, Rosliza (2019)
INTRODUCTION: Secondhand tobacco smoke is a known carcinogen and shown positive association with smoking status, susceptibility and cessation. Smoke free environment policy seem to reduce this exposure and influence intention to quit and frequency of quit attempts. Despite smoke free policy, smokers are still exposed to second hand smoke and this might influence their smoking behaviour and cessation. OBJECTIVES: To examine the association between environmental tobacco smoke exposure with intention to quit smoking among young adult in college with smoke free policy. METHODS: Data were drawn from a cluster based randomised controlled trial in 10 government colleges Selangor. Baseline characteristics of 160 college smoker were measured using adapted questionnaire. Intention to quit was measured using Transtheoretical Model and environmental influence of tobacco smoke exposure. RESULTS: The response rate was 100% (160 students) with majority of the smoker were male (99.4%), single (100%), of Malay ethnicity (94.4%) and Muslim (95.6%). Most of them are in pre-contemplation stage where they do not have any intention to quit (65.6%). On environmental influence, at work or college environmental exposure, majority were exposed between 1 to 2 hours (36.9%) and 3 to 8 hours (40.6%). On exposure at home or hostel, majority were exposed between 1 to 4 hours (44.4%) and 5 to 14 hours (21.9%). On friend's exposures, majority have most of their friend smokers (68.1%). We found no statistically significant association between environmental influence and intention to quit smoking. CONCLUSION: Although we found no relationship, future research should examine the pathway between environmental influence and smoking behaviour.